Planning Crop Production with the Use of Digital Technologies - V. V. Alt; S. P. Isakova (Сельскохозяйственные машины и технологии, 2022)
Agricultural production is shown to be associated with land distribution, variety of agricultural technologies, climatic variability, information diversity, complex algorithms for strategic and tactical decision making. It was noted that the solution to the problem of production planning implies systematizing and structuring the information about technological operations, identifying features and working out parameters for technology selection (adjustment), modeling the agricultural technological process, and the creation of automated information support. The emphasis is placed on the relevance of using modern computers and advanced digital technologies for entering and processing large amounts of information, and visualization of results. (Research purpose) To develop software and technological support enabling the selection of options for technologies adjusted to a particular farm conditions. (Materials and methods) The software was tested in a case of the southern taiga-forest zone of the Novosibirsk region. The process of choosing technologies was studied when cultivating grain crops. A complex of tillage technologies was considered for grain crop cultivation, which ensures minimizing the impact of limiting factors on the yield. Based on the assessment results, invariable and variable factors were identifi ed. The methods used are as follows: information and analytical analysis of materials, a systematic approach, and software development methodologies. (Results and discussion) With the help of the software module, technology options were developed being adjusted to the natural and production conditions of the economy. Registers for technological operations and application conditions were taken as the source material for the formation of options. Two options for selecting technologies were obtained. (Conclusions) As a result, a software module was developed enabling the selection of agricultural technologies based on the thorough accounting and operational processing of information that is used to characterizing the specifi c conditions of the economy, which makes it possible to increase the effi ciency of crop production management and the competitiveness of an agricultural enterprise.